THE CORRELATION BETWEEN LEARNING MOTIVATION AND VOCABULARY SIZE OF STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU BATCH 2020 - Shantika Erina Azel; Novitri Novitri; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is a correlational research design in a quantitative, which used the statistical correlation test in describing and measuring two variables. This research is aimed to investigate the learning motivation and vocabulary size of students of English Study Program of Universitas Riau batch 2020 and to find out whether or not there is any correlation between learning motivation and vocabulary size of students of English Study Program of Universitas Riau batch 2020. Thirty-four students out of 118 students were chosen as the sample students using a random sampling technique. In this research, students’ learning motivation was measured using the Attitude/Motivation Test Battery (AMTB) questionnaire test adapted from Gardner in 2004. While students’ vocabulary size was measured using the Vocabulary Size Test created by Nation in 2007. The findings of this study revealed that the average score of students’ motivation value is 61.26, which is categorized as a fair level of motivation. This study showed that students’ average vocabulary size is 8.650, which can be declared that the sample students’ vocabulary size is on the Mid-frequency level. The result also showed a positive-fair correlation between students’ learning motivation and their vocabulary size, taken from the correlation coefficient value of 0.671 and interpreted based on Sugiyono's (2009) interpretation of correlation.Key Words: Correlation, Learning Motivation, Vocabulary